Модернизация газотурбинного двигателя ДР59Л для газоперекачивающего агрегата ГПА–10 - Коваль, Вячеслав Алексеевич; Беляева, С. О.; Беляев, В. Е.; Ковалева, Е. А. (Eastern-European Journal of Enterprise Technologies, 2009)
The approaches connected with creation of the project modernized gas-turbine engine for газоперекачивающего of the unit by capacity power 20 МWt, executed on the basis of GТE for transportation unit of gas by power 10 МWt are considered. Parameters both the initial engine, and the machine with the new flowing part designed by means of 3-D of a program complex are resulted